(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Kovalchuk I. М. The analysis into the problem of developing professionally significant qualities of a Technology teacher in postgraduate education. The article defines and analyzes the obtained results as for teachers’ idea about the gist and meaning of present-day professionally significant qualities of a Technology teacher, methods of their development as well as the level of motivational readiness of a Technology teacher to professional self-perfection. The author determines that in most cases there is a gap between a Technology teacher’s desire to be an expert in his/her sphere and actual abilities to reach the goal, between teacher’s outward urge towards professional self-perfection and relevant level of inward motivation.